2023
DOI: 10.1159/000533871
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Factors Associated with Response to Golimumab in Japanese Patients with Ulcerative Colitis in Real Clinical Practice: The Phoenix Study

Daisuke Hirayama,
Satoshi Motoya,
Toshifumi Ashida
et al.

Abstract: <b><i>Introduction:</i></b> There have been limited reports on the clinical efficacy of golimumab (GLM) in Japanese patients with ulcerative colitis (UC) in real clinical practice. This study aimed to explore the real-life effectiveness and factors associated with response to GLM in Japanese patients with UC. <b><i>Methods:</i></b> This observational, retrospective, multicenter study was conducted in hospitals with expertise in inflammatory bowel disease treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…This was a retrospective study conducted in the Hokkaido region of Japan using a database originally developed for the P rincipal research in the H okkaido O rganization E mphasizing N utritional and therapeutic I mprovement to IBD patients’ e X pectation (Phoenix) Cohort Study (UMIN Clinical Trials Registry; UMIN000035384), which was initiated in October 2018 and aimed to collect data of patients with IBD and develop new diagnostic criteria and a treatment guideline for IBD. The Phoenix cohort database consisted of data for approximately 2100 patients with IBD who were treated at five core IBD treatment hospitals (Sapporo Medical University Hospital, Hokkaido University Hospital, Asahikawa Medical University Hospital, Sapporo-Kosei General Hospital, and Sapporo Higashi Tokushukai Hospital) between January 1, 1990, and March 31, 2021, which have been used for previous studies of IBD [ 18 , 19 ]. Patient data were collected using medical records and included clinical findings (e.g., treatment details, dosing status, treatment duration, and outcomes), blood test results, endoscopy findings, pathology, and imaging examination findings.…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective study conducted in the Hokkaido region of Japan using a database originally developed for the P rincipal research in the H okkaido O rganization E mphasizing N utritional and therapeutic I mprovement to IBD patients’ e X pectation (Phoenix) Cohort Study (UMIN Clinical Trials Registry; UMIN000035384), which was initiated in October 2018 and aimed to collect data of patients with IBD and develop new diagnostic criteria and a treatment guideline for IBD. The Phoenix cohort database consisted of data for approximately 2100 patients with IBD who were treated at five core IBD treatment hospitals (Sapporo Medical University Hospital, Hokkaido University Hospital, Asahikawa Medical University Hospital, Sapporo-Kosei General Hospital, and Sapporo Higashi Tokushukai Hospital) between January 1, 1990, and March 31, 2021, which have been used for previous studies of IBD [ 18 , 19 ]. Patient data were collected using medical records and included clinical findings (e.g., treatment details, dosing status, treatment duration, and outcomes), blood test results, endoscopy findings, pathology, and imaging examination findings.…”
Section: Methodsmentioning
confidence: 99%
“…A principal research in the Hokkaido Organization Emphasizing Nutritional and Therapeutic Improvement to IBD Patients’ Expectation (Phoenix cohort) study group has previously revealed clinical effectiveness and its predictive factors regarding UST in CD 16 in addition to anti-TNF-α antibodies (infliximab biosimilar and golimumab) in UC and CD. 17 , 18 In this study, using our cohort, we aimed to reveal the clinical effectiveness, remission, persistency, predictive factors associated with effectiveness and persistency, and safety of UST for inducing and maintaining UC remission, thereby contributing to elucidating the appropriate positioning of UST for UC with bio-naïve and bio-failure.…”
Section: Introductionmentioning
confidence: 99%